El tema de la soledad en Góngora, Gustavo Garcia Saravi y Juan Goytisolo - Bączyk Tomaszewska, Emilia (Wydawnictwo Naukowe UAM, 2003)
The aim of this article is to compare two representatives of modern Spanish literature with the Baroque poet, Góngora. Góngora’s distinct influence on the poetry of an Argentinian poet, Gustavo Garcia Saravf and the Spanish prose writer, Juan Goytisolo on the level of content and form may be observed. The author also considers the problem of human fate, marked with suffering and loneliness, which is described by all the three authors from the perspective of a pilgrim.